Analisis Pendekatan Nilai %Ekstraksi Ore North Mainrigde Dengan Metode Bottle Roller Test Di PT. J Resources Bolaang Mongondow - Rangan, Frederico Espinoza; Yanas, Yogi Gautama; Usman, Fahrul Rozzi (Jurnal Teknologi Sumberdaya Mineral, 2024)
The heap leach method is one of the cyanidation processes suitable for low-grade ore and PT J Resources Bolaang Mongondow uses this method in its processing. Column test is the most representative testwork of the heap leach process, but this testwork requires a long time so a faster testwork is needed and can provide %extraction value even though it is less representative and bottle roll test (BRT) is a solution for this. This study aims to estimate the % extraction obtained in cells by the BRT method. From the experimental results, it was obtained that the %extraction value of HG 01 samples at +12, +6, and -6 sizes was 67.1%, 79.2%, and 92.4%, respectively. for LG 02 samples of 68.3%, 81.5%, and 93.9%, for LG 03 samples of 54.5%, 90.6%, and 89.6%, respectively, these three samples are categorized as med-high extraction. While the LG 04 sample was 67.3%, 66.3%, 84.8% and categorized as low extraction.